2022
DOI: 10.3390/buildings12040432
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis and Review of Deep Learning-Based Crack Detection Literature Published between 2010 and 2022

Abstract: The use of deep learning (DL) in civil inspection, especially in crack detection, has increased over the past years to ensure long-term structural safety and integrity. To achieve a better understanding of the research work on crack detection using DL approaches, this paper aims to provide a bibliometric analysis and review of the current literature on DL-based crack detection published between 2010 and 2022. The search from Web of Science (WoS) and Scopus, two widely accepted bibliographic databases, resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 227 publications
0
6
0
Order By: Relevance
“…Today, despite the existence of numerous studies in different fields that use big data and machine learning algorithms it is observed that there are a few studies that examine big data and machine learning through bibliometric analysis. Among these studies, for instance, while Belmonte et al ( 2020 ) examined big data and machine learning simultaneously in their bibliometric analysis, Alonso et al ( 2018 ), Dhamija and Bag ( 2020 ), Tran et al ( 2019 ) focused on artificial intelligence, and Li et al ( 2020 ), Ali et al ( 2022 ), Bidwe et al ( 2022 ), Mao et al ( 2018 ), Nakhodchi and Dehghantanha ( 2020 ) focused on deep learning. Many researchers, including Mishra et al ( 2018 ); Xian and Madhavan ( 2014 ); Liao et al ( 2018 ); Ardito et al ( 2019 ); Liu et al ( 2019 ) and Rialti et al ( 2019 ), Kalantari et al ( 2017 ) have reviewed studies concerning big data.…”
Section: Literaturementioning
confidence: 99%
“…Today, despite the existence of numerous studies in different fields that use big data and machine learning algorithms it is observed that there are a few studies that examine big data and machine learning through bibliometric analysis. Among these studies, for instance, while Belmonte et al ( 2020 ) examined big data and machine learning simultaneously in their bibliometric analysis, Alonso et al ( 2018 ), Dhamija and Bag ( 2020 ), Tran et al ( 2019 ) focused on artificial intelligence, and Li et al ( 2020 ), Ali et al ( 2022 ), Bidwe et al ( 2022 ), Mao et al ( 2018 ), Nakhodchi and Dehghantanha ( 2020 ) focused on deep learning. Many researchers, including Mishra et al ( 2018 ); Xian and Madhavan ( 2014 ); Liao et al ( 2018 ); Ardito et al ( 2019 ); Liu et al ( 2019 ) and Rialti et al ( 2019 ), Kalantari et al ( 2017 ) have reviewed studies concerning big data.…”
Section: Literaturementioning
confidence: 99%
“…The problem of road damage detection using image-based techniques has gained great importance in the last 15 years with the explosion of Computer Vision and Pattern Recognition methods. This rapid growth has led to the publication of numerous surveys comparing different methods, such as [27,49,2]. The proposed methods vary in terms of the type of data analyzed and the approach.…”
Section: Related Datasetsmentioning
confidence: 99%
“…Zhao et al [9] proposed a crack feature pyramid network (Crack-FPN), which has superior feature extraction capability and reduced computational cost. Some research or reviews on the application of objection detection algorithms to crack detection have also been carried out [10][11][12][13][14][15][16]. However, due to the simplicity of the result form, the target detection algorithm is only applicable to simple target existence determination.…”
Section: Introductionmentioning
confidence: 99%